The effect of budgeting based on performance upon the accountability of authority administration of Bogor municipality performance period 2014-2017 - Agung Fajar Ilmiyono (The Accounting Journal of Binaniaga, 2019)
Budgeting based on performance is a type of budget used in public sector activities. This type of budget is influenced by environmental factors that must be predicted to determine the level of uncertainty high or low, so that the objectives for implementing financial reporting performance accountability can be achieved. The purpose of this study is to determine the effect of Budget Planning on Performance Accountability of Bogor municipality administration, to determine the effect of Budget Implementation on Performance Accountability of Bogor municipality administraion and to determine the effect of Performance Evaluation on Performance Accountability of Bogor municipality administration. This research was conducted at the scope of the Bogor municipality administration. This research was conducted at the scope of the Bogor municipality administration. The analytical method used is sample test t and multiple linear regression. the sample chosen using a random sampling method taken from 10 units of the Bogor City Regional Work Unit (SKPD) consisting of 50 respondents. The results of the study showed that Budget Planning and performance evaluation have a positive and significant effect on the Accountability of the Performance of Bogor municipality administration. While Budget Implementation does not affect the Accountability of Performance of Bogor municipality administration.. Keywords: Budget Planning, Budget Implementation, Performance Evaluation, and Performance Accountability